Correlation between event of depression and risk of suicide among productive age in Purwodadi, Grobogan - Agung Tirta Permata Sari, Made; Dewi Wardani, Natalia; G Asikin, Hang (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2024)
Introduction: From 2015 to 2019, 141 people died due to suicide in Grobogan Regency, and Purwodadi district was the third largest after Gabus and Wirosari districts, where most of the suicide perpetrators were of the productive age group. Event of depression is often associated as a risk factor for suicide. Depression is a mood disorder. Depression is characterized by sadness, loss of interest or excitement, feelings of guilt or uselessness, disturbed sleep or appetite, feelings of tiredness, and poor concentration. In its severe form, depression can lead to suicidal thoughts. Purpose: To determine the correlation between the event of depression and the risk of suicide among productive age in Purwodadi, Grobogan. Methods: This research is quantitative research with cross sectional design. The sample in this study consisted of residents of Purwodadi, Grobogan, who are members of Posbindu, using the consecutive random sampling method and bivariate analysis with Fisher's Exact test. The research instrument used a sociodemographic questionnaire, BDI-II questionnaire, and CSSRS. Results: Most of the respondents of productive age in this study (68.6%) did not suffer from depression. There was a significant correlation between the event of depression and the risk of suicide among productive age in Purwodadi, Grobogan (p = 0,002). Conclusions: There was a significant correlation between the event of depression and the risk of suicide.